About New Class of Univalent Starlike Functions - Drbuk ميلاد امحمد; Ahmed عبد السلام رمضان; Omer زينب (Journal of Pure & Applied Sciences, 2021)
In this paper we investigate and define a general class of univalent Starlike functions with respect to a convex domain contained in the right half plane. Also we establish some inclusion relationships associated with the Ruscheweyh Linear operator. Some interesting integral – preserving properties are also considered.